Parental involvement and student academic achievement: a cross-sectional study - Badrasawi, Kamal J I; Yahefu, Humaer; Khalid, Madihah (2017)
PURPOSE Parents’ involvement in children’s education and academic achievement is undeniable. Parental involvement does not have one universal definition and it is not only limited to activities conducted at home. It includes home-based activities, school-based activities as well as parents’ aspiration toward their children’s education. In China, research on parental involvement is still at its primary stages, especially in the rural areas where literature on parental involvement is sparse. Further studies are needed to determine the levels of parental involvement and its role in the academic achievement of school children in these areas. Hence, this study aims to examine the role of parental involvement in the academic achievement of school children in an ethnic minority rural area in China. More specifically, this study examines the levels of parental involvement in the aspect of parents’ educational aspiration, home-based and school-based involvements; the differences in the levels of parental involvement between parents of low and high academic achievement; and the relationships between parental involvement and academic achievement. METHODOLOGY This quantitative research study utilized the cross-sectional survey design method. A 30-item self-constructed questionnaire on parental involvement was used to collect data from 240 parents of third and fourth grade students selected using the non-probability purposive sampling techniques. Five experts from a faculty of education examined the content and face validity of the research instrument. The internal reliability analysis of the questionnaire yielded a Cronbach's alpha coefficient of 0.94. The final collected data were analysed based on the one parameter Rasch modeling for polytomous data using Winsteps Software, version 4.0.1 (2017). Unlike other kinds of analysis, the Rasch Measurement Model transforms raw scores into equal linear measures by using logit units; therefore, it was possible to get the difficulty measure for each item and for each person. The Rasch Item-Person Maps also made possible to place all the items and persons on one interval scale, and display clearly the position of each item and each person in relation with other items and persons distributed on both sides of the scale. The most difficult items and most able person are placed at the top of the scale and the easiest items and least able persons are positioned at the lower part of the scale. The Rasch person interval data files were analyzed using the Statistical Package for the Social Sciences (SPSS), version 23. The independent sample t-test was used to examine the differences in the mean scores of parental involvement. The Bivariate Pearson product-moment correlation coefficient (r) wasused to examine the relationships between parental involvement and student academic achievement. RESULTS Overall, it was likely easy for the participating parents to endorse the three categories of parental involvement as indicated by the Mean of person ability (endorsement) measure (0.79 logit), higher than the Mean of item difficulty (0.0 logit). The easiest category to be endorsed by the parents was the Aspiration (Mean= -.681 logit), followed by Home-Based Involvement (Mean= -.036 logit) and School-Based Involvement (Mean= .717 logit). However, the items in each category showed different distributions/order; either they are placed towards the top of the scale, in the middle, or towards the lower positions of the scale There was a statistically significant difference in the mean scores of parental involvement between parents of high and low achieving school children. There was also a statistically significant positive correlation between parental involvement and student academic achievement. CONCLUSIONS This is the first study conducted on parental involvement and its role in the academic achievement of primary school children in an ethnic minority rural area in China; therefore, the results are useful to school administrators, teachers, parents, and children. It has provided necessary information on the levels of parents’ educational aspiration, home-based involvement, and school-based involvement. Overall, the participating parents were involved in their children’s education. The maps produced by the Rasch model have made possible to clearly see the positions of each item and parent on one interval scale. Parents of high achieving school children were more involved in their children’s education. There was a significant positive relationship between parental involvement and student academic achievement. School administrators and teachers may take action to encourage partnership between parents and teachers in order to improve children’s achievement. Further qualitative research is recommended to get more in-depth information on parental involvement in all aspects and the challenges to parental involvement.